Inquiry-Discovery Empowering High Order Thinking Skills and Scientific Literacy on Substance Pressure Topic - Wartono, Wartono; Takaria, Johannis; Batlolona, John Rafafy; Hudha, Muhammad Nur; Jayanti, Y. M. (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
Inquiry-discovery learning plays an important role in improving high-order thinking skills (HOTS) and scientific literacy (SL). In this HOTS and SL research, it was designed with Inquiry-discovery based learning. The purpose of this study was to promote Inquiry discovery models in empowering higher-order thinking skills and scientific literacy in physics with different classes. This research used Quasi-Experimental Design research, and Pretest-Posttest Control Group Design. The research analysis design matrix used two-way ANOVA. The sample was taken from two classes, namely the experimental and control classes of 68 students. The results of the study prove that Inquiry discovery can improve HOTS and SL physics of students. Thus, inquiry-discovery can be recommended to increase student's HOTS and SL physics when compared to conventional classes. The novelty of this study is that inquiry-discovery learning models are more likely to reconstruct students' scientific knowledge of physics on aspects of HOTS and SL with real-world life.